Growth Of Spinach (Amaranthus tricolor L.) Under Various Applications of Nutrient Concentrations in Hydroponic System of Nutrient Film Technique - Sindy Sella Rukmi; Aiyen Aiyen; Abdul Rauf (AGROLAND The Agricultural Sciences Journal (e-Journal), 2017)
The research aimed to discover the response of the growth of two spinach species on Nutrient Film Technique (NFT) hydroponic system and the concentration of the appropriate AB Mix solution on each species. The research was conducted in January to February 2016, at Green House, Faculty of Agriculture, Tadulako University by using Split Plot Design method. The main plot was red and green spinach, while the subplot was the concentration of AB Mix nutrient solution, namely 4 ml/L of water, 5 ml/L of water, 6 ml/L of water and 7 ml/L of water. The research findings reveal that AB Mix nutrient solution was generally very good to support the growth of spinach on NFT hydroponic. The green spinach had better response rather than the red one. There was no interaction between species and the concentration of nutrient solution. The good concentration of nutrient solution for green spinach is 6 ml/L. It was showed by the better growth of plant height on all age of plant, the more number of leaves, the canopy and the root (wet and dry) were heavier, while on the red spinach, 5 ml/L of concentration of nutrient solution resulted in the best growth, yet it was not significantly different from other concentration except on the parameter of plant height and the dry weight of plant canopy.